2022
DOI: 10.1007/s12237-021-01035-9
|View full text |Cite|
|
Sign up to set email alerts
|

Variability in Carcinus maenas Fecundity Along Lagoons and Estuaries of the Portuguese Coast

Abstract: Although Carcinus maenas as a species is widely studied, research focusing on fecundity is still scarce. The main objective of this study was to evaluate size-fecundity relationships across different lagoons and estuaries, along the Portuguese coast, to understand how the local environment affects reproductive patterns. Between 2019 and 2020, ovigerous females were collected from the Southern (Ria Formosa and Ria de Alvor), Central (Rio Sado) and Northern regions (Ria de Aveiro) of Portugal, and the fecundity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
(83 reference statements)
0
0
0
Order By: Relevance
“…Ovigerous females were more abundant in this lagoon in the winter period, which has also been reported for other areas of the Portuguese Atlantic coast (Baeta et al 2005, Queiroga et al 1994. The estimated carapace width of females at maturity was 45.11 mm, which is lower than the sizes reported for North Wales or southwest Ireland (Reid et al 1997, Lyons et al 2012) and lower than the sizes reported for other Portuguese brackish water systems except the Sado estuary (Monteiro et al 2022).…”
Section: Discussionsupporting
confidence: 60%
“…Ovigerous females were more abundant in this lagoon in the winter period, which has also been reported for other areas of the Portuguese Atlantic coast (Baeta et al 2005, Queiroga et al 1994. The estimated carapace width of females at maturity was 45.11 mm, which is lower than the sizes reported for North Wales or southwest Ireland (Reid et al 1997, Lyons et al 2012) and lower than the sizes reported for other Portuguese brackish water systems except the Sado estuary (Monteiro et al 2022).…”
Section: Discussionsupporting
confidence: 60%
“…This implies that populations from warmer locations can reproduce at smaller sizes at the cost of reaching smaller maximum sizes. This finding could be directly related to fecundity, given the close relationship between female size and the number of eggs [8,62]. Temperature also has an influence on egg size [71,72].…”
Section: Reproductive Traitmentioning
confidence: 87%
“…Carcinus maenas is an euryhaline intertidal species, adapted to live in a wide range of salinity and oxygen conditions [10] and thus inhabiting different systems (lagoons, estuaries, etc. ), with local conditions affecting populations biological traits [10,62]. Oxygen solubility increases as both salinity and temperature decrease [63], and, in a previous study [61], it was observed that the maximum size of crustacean species is influenced by oxygen availability.…”
Section: Morphological Traitmentioning
confidence: 93%
See 2 more Smart Citations